Cell-based glycoengineering for production of homogeneous and specific glycoform-enriched antibodies with improved effector functions - Han-Wen Huang; Yi-Fang Zeng; Vidya S. Shivatare; Tzu-Hao Tseng; Chi-Huey Wong (Proceedings of the National Academy of Sciences, 2025)
Glycosylation of humanized antibody at Fc-Asn297 significantly affects the Fc-mediated killing of target cells through effector functions, especially antibody-dependent cellular cytotoxicity (ADCC), antibody-dependent cell-mediated phagocytosis (ADCP), and antibody-dependent vaccinal effect (ADVE). Previous studies showed that therapeutic immunoglobulin G (IgG) antibodies with α2,6-sialyl complex type (SCT) glycan attached to Fc-Asn297 exhibited optimal binding to the Fc receptors on effector cells associated with ADCC, ADCP, and ADVE. However, the production of antibodies with homogeneous Fc-SCT glycan requires multiple in vitro enzymatic and purification steps. In this study, we report two cell-based methods to produce Fc-GlcNAc antibody and Fc-SCT-enriched antibodies with improved effector functions. First, we expressed endoglycosidase S2 in Expi293F GnT1- cells to trim all N-glycans to Fc-GlcNAc antibody for in vitro transglycosylation to generate homogeneous antibodies with well-defined Fc glycan. Second, we engineered the glycosylation pathway of HEK293T cells through knock-out of undesired glycosyltransferases and knock-in of desired glycosyltransferases to produce Fc-SCT-enriched antibodies and evaluated their binding to Fc receptors, and we found that the Fc-SCT-enriched antibody is like or better than the homogeneous Fc-SCT antibody in binding to the Fc receptors associated with ADCC, ADCP, and ADVE.